PERBEDAAN INDEKS ERITROSIT SEBELUM DAN SESUDAH PEMBERIAN SUPLEMEN Spirulina platensis PADA PENDERITA DIABETES MELITUS TIPE 2 DI PUSKESMAS WARU SIDOARJO - Alifiah, Salsabiil Rochman; Suhariyadi, Suhariyadi; Evy Diah , Woelansari (Politeknik Kesehatan Kementerian Kesehatan Surabaya, 2021)
Diabetes mellitus type 2 is a metabolic disease that occurs due to abnormalities in insulin secretion, insulin action or both. One of the most common disorders in the body system is the red blood cell index consisting of MCV, MCH and MCHC. Spirulina platensis is a blue-green microalgae that contains phycocyanin so that it can increase hemoglobin levels, erythrocytes and blood profile in the bone marrow. The purpose of this study was to determine the difference before and after giving Spirulina platensis supplementation for 10 days on the erythrocyte index in patients with type 2 diabetes mellitus. This type of research was one group pretest-posttest. This research was conducted at the Waru Community Health Center, Sidoarjo Regency from December 2020 to May 2021. The results showed that the mean value of MCV decreased before: 80.19 fl and after: 80.1 fl. Meanwhile, the average value of MCH and MCHC increased, namely MCH before: 27.57 pg and after: 27.68 pg, then MCHC before: 34.33 g / dL and after: 34.51 g / dL. In the third statistical test, the significance value (p-value), namely the MCV (0.863), MCH (0.773) and MCHC (0.627) shows that (p> 0.05), it can be concluded that there is no significant difference before and after supplementation. Spirulina platensis on the erythrocyte index (MCV, MCH and MCHC) in people with type 2 diabetes mellitus.